مقاربة في البنية السيكولوجية للزمن "الصابئة" أنموذجاً - الجبرين, أمينة (جامعة الوادي - University of Eloued, 2020)
ملخص: يقدّمُ هذا البحث الموسوم بــــ" مقاربة في البنية السيكولوجية للزمن "الصابئة" أنموذجاً"، دراسةً لمنجزٍ سرديٍّ نسائي سعودي تلك هي رواية "الصابئة" للروائية السعودية "حنان القعود". يحضر الزمن في الرواية بوصفه أحد أهم العناصر المشكّلة للسرد الروائي، ونظراً لكون النص الروائي نصّاً حياتياً، فذلك يعني أنّه نصٌّ زمني. ويشكل الزمن النفسي أحد أهم أنماط الزمن ارتباطاً وتجسيداً للحالات الشعورية، وانطلاقاً من ذلك، يسعى هذا البحث إلى دراسة الزمن النفسي في رواية "الصابئة"، من خلال الوقوف عند الدلالات الشعورية للذات وسط تداخل الأزمنة وتشابكها، كما يسعى أيضاً إلى الكشف عن تحوّلات الذات وتغيّراتها وفقاً لتحوّلات الزمن، ويسعى أيضاً إلى رصد سلطة الزمن وهيمنته على الذات، وانعكاس ذلك كله على الحالات الشعورية والوجدانية لها. الكلمات المفتاحية: البنية، مقاربة، الزمن ، الصابئة، النفسي. Abstract This research entitled "An Approach to the Psychological Structure of Time: "AS-Sααbiah novel as a Model" studies the Saudi feminine narrative achievement of Hanan Alqu-oud's, the Saudi novelist, novel: "AS-Sααbiah ". Time is present in the novel as one of the important elements which form a narration. The fact that the narrative text is about life means it is temporal. Psychological time is one of the most important time patterns that relate to and embody consciousness states. Hence, based on this, this research seeks to examine the psychological time in the novel: "AS-Sααbiah" through exploring the consciousness significances of the self amid the overlapping and intertwining of times. Moreover, it seeks to reveal the transformations and changes of the self along with the transformations of time. It also seeks to monitor the power of time and its dominance over the self, and how they affect its affective and consciousness states. key words: Structure, Approach, Time, AS-Sααbiah, Psychlogical.
مقال
Keywords: البنية مقاربة الزمن الصابئة النفسي